THE INTERACTION OF HUMAN RESOURCE MANAGEMENT AND MANAGEMENT IN ENSURING COMPETITIVENESS IN BUSINESS (Marketing Journal, 2025)
This article provides a theoretical analysis of the interaction between human resource management and management strategies in enhancing the competitiveness of entrepreneurial entities. The study is based on the resource -based view and human № 1 550 capital theory. The impact of high -performance work systems, strategic HRM practices, and transformational leadership on employee motivation and organizational performance has been identified. A conceptual model for achieving competitive advantage through the alignment of SHRM and management was developed. Existing theories were evaluated based on academic literature, empirical research findings were summarized, and practical recommendations were proposed. The importance of a strategic approach to human res ources was scientifically substantiated.
Keywords: competitiveness; human resource management; strategic management; human capital; high -performance work systems; transformational leadership; employee engagement; strategic HRM; organizational performance; resource -based view